Calcification score evaluation in patients listed for renal transplantation. Issue 3 (13th February 2017) - Kahn, Judith; Ram, Leona Marleen; Eberhard, Katharina; Groselj‐Strele, Andrea; Obermayer‐Pietsch, Barbara; Müller, Helmut
Abstract: Based on native CT scans of the pelvic region using a standardized calcification score, evaluation of iliac vascular calcification was performed between 2008 and 2012 prior to listing for renal transplantation in 205 patients with chronic kidney disease. Vascular calcification showed a decrease from proximal to distal. The difference between the degree of calcification in the common iliac artery and in the external iliac artery was significant ( P <.001). Risk factors for total iliac vascular calcification were age, smoking, sex, underlying renal disease, and diabetes. Multivariate analysis revealed age to be the most relevant risk factor ( P <.001). The duration of hemodialysis correlated significantly with total iliac vascular calcification. As the introduction of the standardized surgical evaluation protocol, no transplantation has had to be broken off and no early graft loss due to calcification has occurred. Thus, careful scoring of vascular calcification prior to transplantation may be a valuable tool to support surgical decisions and to improve patient safety and outcome in increasingly older transplant recipients.